2020
DOI: 10.1007/s00259-020-04969-7
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of 18F-FDG-PET among memory clinic patients with uncertain diagnosis

Abstract: Purpose To assess the clinical impact and incremental diagnostic value of 18 F-fluorodeoxyglucose (FDG-PET) among memory clinic patients with uncertain diagnosis. Methods The study population consisted of 277 patients who, despite extensive baseline cognitive assessment, MRI, and CSF analyses, had an uncertain diagnosis of mild cognitive impairment (MCI) (n = 177) or dementia (n = 100). After baseline diagnosis, each patient underwent an FDG-PET, followed by a post-FDG-PET diagnosis formulation. We evaluated (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 47 publications
(75 reference statements)
1
20
0
Order By: Relevance
“…Moreover, use of FDG-PET has also been recommended by the European Association of Nuclear Medicine and the European Academy of Neurology (EANM-EAN) both in people with dementia ( Nobili and others 2018 ) and in mild cognitive impairment (MCI) ( Arbizu and others 2018 ; Nobili and others 2018 ). Recently, it has been observed that FDG-PET has significant clinical utility not only for early diagnosis but also helps in differential diagnosis of people with uncertain diagnosis of dementia ( Perini and others 2020 )…”
Section: Fdg-pet Imaging In Admentioning
confidence: 99%
“…Moreover, use of FDG-PET has also been recommended by the European Association of Nuclear Medicine and the European Academy of Neurology (EANM-EAN) both in people with dementia ( Nobili and others 2018 ) and in mild cognitive impairment (MCI) ( Arbizu and others 2018 ; Nobili and others 2018 ). Recently, it has been observed that FDG-PET has significant clinical utility not only for early diagnosis but also helps in differential diagnosis of people with uncertain diagnosis of dementia ( Perini and others 2020 )…”
Section: Fdg-pet Imaging In Admentioning
confidence: 99%
“…Therefore, the need for earlier and more accurate detection of AD becomes critical. The earliest detectable changes in AD are neuropathological which are diagnosed by functional brain imaging, i.e., positron emission tomography (PET) [1] and magnetic resonance imaging (MRI) [2]. Additional diagnostic tests in clinical routine practice entail the use of the core AD cerebral spinal fluid (CSF) biomarkers, i.e., phosphorylated TAU, total TAU, and the Aβ 1-42 /Aβ 1-40 ratio [3].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, important clinical studies are been carried out to stablish the clinical impact of amyloid and 18 F-FDG PET in the clinical practice (11)(12)(13)(14)(15). Although there is now significant evidence about the clinical impact of incorporating these tools in the assessment of patients with cognitive impairment, most of the literature comes from high-income countries.…”
Section: Introductionmentioning
confidence: 99%